Immunochemical characterization of a new platelet specific monoclonal antibody and its use to demonstrate the cytoskeletal association of the platelet glycoprotein IIb-IIIa complex. Issue 3 (March 1986) - Bird, Christopher; Callus, Marion; Trickett, Lynne; Thorpe, Robin
Abstract : We describe the production and characterization of a monoclonal antibody specific for platelets. This antibody reacts strongly with human and primate platelets, but does not recognise human monocytes, polymorphonuclear leucocytes, lymphocytes, erythrocytes, leukaemic nor fibroblast cell lines, nor rodent platelets. Immunoprecipitation studies using radiolabelled platelet membrane proteins showed that the monoclonal antibody binds to the platelet membrane glycoprotein IIb-IIIa complex. Affinity chromatography using immobilized monoclonal antibody allows purification of the antigen, but also co-purifies the cytoskeletal proteins actin and myosin. Our results demonstrate immunochemically that although the GP IIb-IIIa complex is an external structure, it is connected through the cell membrane to the microfilament system.